The Influence of Promotion and Call to Action (CTA) Strategies in TikTok Content on Purchase Decisions among USK Students with Religiosity as a Mediating Variable - Wirdaus Wirdaus; Teuku Meldi Kesuma; Fitrah Afandi (Universitas Syiah Kuala, 2026)
The development of digital technology has transformed consumer behavior, including through social media platforms like TikTok, which have now become tools for promotion and sales. This study analyzes the influence of promotion and Call to Action (CTA) strategies on the purchasing decisions of students at Universitas syiah kuala (USK), with religiosity as a mediating variable. Using a quantitative method with path analysis and the Sobel test, the results show that both promotion and CTA have a positive and significant effect on purchasing decisions, while religiosity does not mediate the relationship between promotion and CTA and purchasing decisions. These findings indicate that although USK students tend to have high religiosity, they are inclined to make purchasing decisions based on visual, emotional, and instant promotional aspects. The implications of this research are expected to serve as a reference for digital marketers, business actors, and content creators in designing more effective marketing strategies that align with consumer values